Efektivitas Konseling Kelompok Dalam Meningkatkan Karakter Sopan Santun Bagi Siswa Keturunan Dayak Bakumpai Di Sekolah Menengah Atas (SMA) Negeri 1 Marabahan - Akhmad Rizki Ridhani; Zainal Fauzi; Sanjaya (INSIGHT: Jurnal Bimbingan Konseling, 2026)
The character of good manners is one of the important aspects in character education that plays a role in shaping students' personalities so they are able to interact well in the social environment. However, in recent years, there has been a decline in the character of good manners among students, including students of Dayak Bakumpai descent. Globalization factors, the influence of social media, and the lack of intensive character education in schools are the main causes of this phenomenon. Therefore, this study aims to examine the effectiveness of group counseling in improving the character of good manners of Dayak Bakumpai students of SMA Negeri 1 Marabahan. This study used a quasi-experimental method with a Pretest-posttest One Group design. The research sample consisted of 10 students selected using a purposive sampling technique and divided into experimental and control groups. Data were collected through observation, scales, interviews, and documentation, then analyzed using descriptive and inferential statistical techniques, including paired sample t-tests and independent sample t-tests.